2016
DOI: 10.3389/fpls.2016.01782
|View full text |Cite
|
Sign up to set email alerts
|

Root-to-Shoot Hormonal Communication in Contrasting Rootstocks Suggests an Important Role for the Ethylene Precursor Aminocyclopropane-1-carboxylic Acid in Mediating Plant Growth under Low-Potassium Nutrition in Tomato

Abstract: Selection and breeding of rootstocks that can tolerate low K supply may increase crop productivity in low fertility soils and reduce fertilizer application. However, the underlying physiological traits are still largely unknown. In this study, 16 contrasting recombinant inbred lines (RILs) derived from a cross between domestic and wild tomato species (Solanum lycopersicum × Solanum pimpinellifolium) have been used to analyse traits related to the rootstock-mediated induction of low (L, low shoot fresh weight) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 68 publications
2
17
0
1
Order By: Relevance
“…Interestingly, the ACC levels were depressed in the tolerant LcHp rootstocks, which showed increased growth under low-P. These ACC responses in contrasting rootstocks under low-P were similar to those observed under low-K ( Martínez-Andújar et al, 2016 ), and under non-stress conditions in hydroponics ( Cantero-Navarro et al, 2016 ), suggesting that ethylene-precursor is a constitutive or stress-induced root-to-shoot negative signal regulating shoot growth.…”
Section: Discussionsupporting
confidence: 62%
See 2 more Smart Citations
“…Interestingly, the ACC levels were depressed in the tolerant LcHp rootstocks, which showed increased growth under low-P. These ACC responses in contrasting rootstocks under low-P were similar to those observed under low-K ( Martínez-Andújar et al, 2016 ), and under non-stress conditions in hydroponics ( Cantero-Navarro et al, 2016 ), suggesting that ethylene-precursor is a constitutive or stress-induced root-to-shoot negative signal regulating shoot growth.…”
Section: Discussionsupporting
confidence: 62%
“…Besides P, xylem Ca concentration was also correlated with SDW and RDW under both high and low-P conditions ( Table 1 ). Constitutive rootstock capacities to uptake Ca and to maintain high foliar Ca concentrations seem related to the general vigor ( HcHp ) and adaptability to low-P ( LcHp ), as under low-K conditions ( Martínez-Andújar et al, 2016 ). The positive role of Ca in adaptation to low-P was supported by the consistent correlation between xylem Ca and P concentrations ( r = 0.6, P ≤ 0.01), and with RDW under low-P, suggesting that root biomass significantly influences the uptake of those nutrients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The t ZR, apart from being in the cambium, is generally abundant in the xylem sap (Hirose et al ). Interestingly, in tomato plants subjected to K‐deficiency the amount of t ZR in root xylem sap has been found inversely correlated to the presence of ethylene precursor, 1‐aminocyclopropane‐1‐carboxylic acid (ACC), which controls the expression of the ERF gene thereby regulating root development and root‐shoot communication (Martínez‐Andújar et al ). Based on above, the t ZR accumulation in the concave Xy dev could be associated with the complete absence of ACC oxidase and the concomitant decrease of ERF protein levels observed in the later stages of bending stress (De Zio et al ), regulating wood development and/or deposition of cell wall polymers (Vahala et al , Rossi et al ).…”
Section: Discussionmentioning
confidence: 99%
“…The increased contents of soluble solids in fruits with the increased potassium fertilization occurs by the transport of sucrose in the phloem, which is favored by potassium. This, in turn, potentiates the transport from leaves to fruits, meeting the source-drain relation (Coskun et al, 2016;Martínez-Andújar et al, 2016). Rebouças Neto et al (2016) worked with the hybrid Dominador F1 of the persimmon group and also observed an increase in the concentration of total soluble solids as potassium doses increased.…”
Section: Resultsmentioning
confidence: 95%